The Factors of Successful Family Business: a Study on Consumer Durable Sector: Exploring the Influence of Purchase Behavior on the Success of Family Businesses in the Consumer Durable Sector (Journal of Advances and Scholarly Researches in Allied Education, 2014)
An understanding of purchase behaviour of consumers towards durablegoods is essential as it reflects the influence of brands, price, quality,quantity, mode of purchase, etc. The success of the market or the failuredepends on the purchase behaviour of consumers. Consumer is nerve centre of themodern marketing, understanding his behaviour is quite essential for efficientand effective marketing management. Customers may state their needs, wants butact otherwise. They may not be in touch with their deeper motivations. India’sconsumer market is riding the crest of the country’s economic boom. Driven by ayoung population with access to disposable incomes and easy finance options,the consumer market has been throwing up staggering figures. Marketing problemsconfronted from the consumers‟ behaviour has a greater degree of similaritywith behavioral problems. The use of durable goods is becoming increasinglypopular in recent years in India.